Review on applications of ultrasonic treatments in meat industry - Nagy, Dávid; Lambertné Meretei, Anikó; Zsom, Tamás; Zsomné Muha, Viktória (Animal welfare, Ethology and Housing Systems (AWETH), 2018)
The food industry is facing ever greater challenges by the increasing number of people in our society, since it has to provide, beside of quality, an increasing amount of safe and nourishing food using environmentally friendly and economic process. The meat industry is placing great emphasis on quality, rheological properties (such as texture and tenderness). They are also aware of the importance of decontamination, microbial inactivation and recontamination even during long-term storage. Many studies showed that the application of ultrasonic treatment alone or combined with other processing or preservation methods provides the potential to improve the general quality, marination and tenderness of meat, preventing microbial growth in meat and meat products. Using ultrasonic methods has many beneficial properties not just for the meat industry, but even for consumers, because these products need less time and less invested energy to be fried or cooked. Our main purpose with this article is to provide an overview about the possibilities and advantages of the ultrasonic methods in industrial environment, the effect of these methods on texture, nutritional value and also the bacterial environment of the meat and meat products.